Perbedaan Penerapan Higiene Sanitasi Berdasarkan Tingkat Pengetahuan Penjamah Makanan di RSUD Tabanan Provinsi Bali - Purnamsi DD, Kadek Ayu; Yuni Gumala, Ni Made; Ariati, Ni Nengah (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
The level of knowledge of sanitary hygiene of food handlers greatly affects how the attitude of food handlers in processing food, if the level of knowledge of sanitary hygiene of food handlers is less then the application of personal sanitary hygiene per person will be less and vice versa because the level of knowledge greatly affects the attitude of how to apply sanitary hygiene. This study aims to determine the differences in the application of sanitary hygiene based on the level of knowledge of food handlers at Tabanan Regional Hospital. The type of research used is observational with a cross sectional design. The research sample was food handlers at the Nutrition Installation of Tabanan Regional General Hospital as many as 30 people. The data collected include the level of knowledge and application of sanitary hygiene of food handlers using questionnaires. To determine the difference between the application of sanitary hygiene based on the level of knowledge of food handlers, an independent analysis of t-test was carried out. The results showed knowledge of the application of sanitary hygiene with good categories as many as 16 people (53.3%) and sufficient categories as many as 3 people (100.0%). The results showed knowledge of the application of sanitary hygiene with good categories as many as 16 people (53.3%) and sufficient categories as many as 3 people (100.0%). The results of the analysis show that there is a difference between knowledge and the application of sanitary hygiene of food handlers with the results p = 0.000 (p 0.005).Keywords: Application of sanitation hygiene, knowledge level